Comparison of Real-time Polymerase Chain Reaction and Culture for Targeting Pathogens in Pediatric Severe Community-Acquired Pneumonia - Khai Quang Tran; Van Hung Pham; Chau Minh Vo; Quan Minh Pham; Phuong Minh Nguyen (AVES Yayincilik, 2024)
Objective: This study aims to determine the frequency of pathogen detection by real-time polymerase chain reaction (PCR), the frequency of pathogen isolation by culture; and compare the value of real-time PCR and culture of nasopharyngeal aspiration samples in patients with severe community-acquired pneumonia (sCAP). Materials and Methods: It was a prospective and descriptive study. All pediatric patients diagnosed with sCAP were performed real-time PCR and culture of nasopharyngeal aspiration samples. Results: A total of 336 patient samples were obtained from children with sCAP. Real-time PCR detected pathogens in 312 patients (92.9%), while culture isolated bacteria in 228 patients (67.9%). Coinfections were reported in 279 cases (83.0%) through real-time PCR. The frequency of agreement between culture and real-time PCR was quite high (P < .001). Conclusion: Real-time PCR demonstrated more ability for detecting microorganisms than culture. This finding highlighted the value of real-time PCR for targeting pathogens in children with sCAP, particularly in cases involving complex pathogens or those requiring timely identification.